2019
DOI: 10.1212/nxi.0000000000000531
|View full text |Cite
|
Sign up to set email alerts
|

HIV is associated with endothelial activation despite ART, in a sub-Saharan African setting

Abstract: ObjectiveTo study the relationship between endothelial dysfunction, HIV infection, and stroke in Malawians.MethodsUsing a cross-sectional design, we measured plasma levels of intercellular adhesion molecule-1 (ICAM-1), plasminogen activator inhibitor-1 (PAI-1), vascular endothelial growth factor (VEGF), and soluble thrombomodulin (sTM) in stroke patients and controls, stratified by HIV status. These biomarkers were measured using ELISA. After dichotomization, each biomarker was used as the dependent variable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Vascular endothelial growth factor-D (VEGF-D) is a secreted protein that can promote the remodeling of blood vessels and lymphatics in development and disease ( 35 ). While their increase could indicate normalization of endothelial integrity and activity on ART, recent evidence suggests that HIV-1 associated endothelial activation persists despite ART ( 36 ). Due to increased rates of cardiovascular disease among people living with HIV-1, this is an important area to explore in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor-D (VEGF-D) is a secreted protein that can promote the remodeling of blood vessels and lymphatics in development and disease ( 35 ). While their increase could indicate normalization of endothelial integrity and activity on ART, recent evidence suggests that HIV-1 associated endothelial activation persists despite ART ( 36 ). Due to increased rates of cardiovascular disease among people living with HIV-1, this is an important area to explore in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Viral load was rarely described. Kamtchum-Tatuene et al reported a median viral load of 1,884 copies/ml, with 55.6% of participants having > 1,000 copies/ml; while in a South African study, 62.5% of patients were not virologically suppressed, despite many patients reporting being on ART [ 31 , 32 ]. The use of ART was well described, and as shown in Table 2 , coverage was generally poor (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular endothelial growth factor-D (VEGF-D) is a secreted protein that can promote the remodeling of blood vessels and lymphatics in development and disease (22). While their increase could indicate normalisation of endothelial integrity and activity on ART, recent evidence suggests that HIV-1 associated endothelial activation persists despite ART (23). Due to increased rates of cardiovascular disease among people living with HIV-1, this is an important area to explore in further studies.…”
Section: Discussionmentioning
confidence: 99%